Peripartum Cardiomyopathy: A Case Report - Ozlem Ece Basaran; Emine Seda Guvendag Guven; Suleyman Guven (Gynecology Obstetrics & Reproductive Medicine)
Peripartum cardiomyopathy is one of the potentially life-threatening complications of pregnancy. It is characterized by symptoms of heart failure in the last months of gestation or within five months after birth. The objective of this case report was to report a case of peripartum cardiomyopathy.